Review on the Biology of Purpleback Flying Squid in South China Sea - Jiangtao, Fan; Xue, Feng; Yongsong, Qiu; Zirong, Huang; Guobao, Chen (Animal husbandry and feed science, 2015)
Purpleback flying squid （Sthenoeuthis oualaniensis） is an important marine economic species, studying its biological characteristics is very important for the resource assessment and management. This paper summed up domestic and international information of squid biology, and showed some details on this subject. According to the squid life history ：egg, larvae, juveniles and adult fish stage, it summarized from the age of growth, population structure, migration, spawning, vertical distribution, habitat, and status of resources. There is little research on the squid larvae and the signs of juveniles period ended are not clear. Adult fish is divided into four main populations and two minor popular ons, the large group, medium-sized group, small group and mini-group, while medium-sized groups can be divided into medium uniaxial group and medium-sized biaxial according to the characteristics of the inner shell. The distribution of purpleback flying squid has the ＂island correlation＂, it usually ascend to the surface at night and drop to the deep-water during the daytime. Purpleback flying squid plays an important role in the ecosystem. It is the main food of many fish, and marine mammals ; also it is the predators of crustaceans and small fish. It has the self-feed characteristics. Purpleback flying squid widely distributes in the 38 °N to 40°S tropical and subtropical waters, especially in the South China Sea, the catchability is （130 -200）×10^4 tons in one year.